Proposta di riqualificazione e valorizzazione del mercato coperto di Honda (Tolima, Colombia) = Proposal for the redevelopment and enhancement of Honda's covered market (Tolima, Colombia) (2021)
The purpose of this thesis is to study Honda's market (composed of one historic building and other annexed buildings) and its context based on the concepts of revitalization, enhancement, and refunctionalization. On that basis, we intend to formulate key interventions at the master plan and architectural level that solve current problems by enhancing the existing potential. To this end, the case study is structured on four lines: the first is the theoretical, historical, and regulatory review at different scales (territorial, local and specific market); the second is the collection of data on the site starting from phenomenological observation and architectural, planimetric and photographic surveys; the third is the analysis of the data obtained both in the bibliographic review and in practice; finally, the fourth is the formulation of intervention proposals at masterplan and architectural scales with emphasis on the listed historic building. The analysis led to the understanding of the complexity of the relationship between the market and the territory in which it is located to understand the building in its materiality and to arrive at an approach to the tension existing between the architectural work and the use that people make of it in daily life. Consequently, the most important problems were understood in order to arrive at coherent solution proposals that transcended purely physical interventions to move to solutions of revitalization, enhancement, and re-functionalization. Finally, this study can contribute to arousing interest and sensitivity in the exercise of architectural design in which the purely material perspective is broadened in order to explore the boundaries between the way in which people use spaces and how they appropriate them. Likewise, the thesis proposes specific solutions and interventions both at a territorial and architectural level that could act as a guide for future interventions in the city of Honda and its covered market.